THE NESJAVELLIR HIGH TEMPERATURE GEOTHERMAL FIELD IN ICELAND - Stefansson, V. (Stanford University, 1985)
The Nesjavellir High Temperature Geothermal Field is located in the Northern part of the Hengill Geothermal Area, which has been estimated to be one of the largest geothermal areas in iceland. Drilling started at Nesjavellir some 20 years ago with five wells. In 1982 a renewed exploration phase began and five additional wells have been drilled during the last three years. The pressure distribution within the geothermal system is very inhomogeneous in both horizontal and vertical directions. Variations in temperature are also considerable. The highest pressure and temperature is found in the southwestern part of the investigated area and both pressure and temperature decreases towards northeast. There seem to be four different zones of pressure potential in the system, which require the existence of both horizontal and vertical barriers in the system. Some parts of the geothermal system are in two-phase condition whereas other parts are in single phase liquid condition. The chemical composition of the fluid seem to be relatively uniform and a common origin of the fluid is assumed. The transmissivity of wells is in the range (1,3-3,5) 10{sup -8} msup 3/Pa {center_dot} s whereas the flowing enthalpy ranges from 1200-2100 kJ/kg. The thermal output of wells are 40-60 MW. The geothermal system at Nesjavellir shows a high degree of three-dimensional variation, but a simple conceptual model described in the paper, seem to be in agreement with all observation made so far in the field.